Characteristics of In-Hospital Mortality among Patients with Acute Coronary Syndrome: A Single-Center Study in West Java, Indonesia - Dennis Bonang Tessy; Miftah Pramudyo; Charlotte Johanna Cool (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Acute Coronary Syndrome (ACS) is a severe manifestation of coronary artery disease, classified into unstable angina (UA), non-ST-segment elevation myocardial infarction (NSTEMI), and ST-segment elevation myocardial infarction (STEMI). In-hospital mortality in patients with ACS remains high despite the advancement of therapy. This study aimed to evaluate the characteristics of in-hospital mortality among ACS patients in West Java, Indonesia.Methods: This descriptive cross-sectional study analyzed retrospective secondary data of ACS patients who died during hospitalization in the period of July 2018 to June 2019 that were recorded in the ACS registry.Results: A total of 17 patients died during hospitalization in the study period. The mean age was 64.1 years, predominantly female (n=10). The prevalent diagnoses were STEMI (n=11) and NSTEMI (n=6). Interestingly, no patients had died from UA. Hypertension was the most frequent risk factor (11 of 17). Mortality among Killip Class I, II, III, and IV were 7, 5, 1, and 4 patients, respectively. The number of patients who died after underwent Percutaneous Coronary Intervention (PCI) was lower (n=6) than those who did not undergo PCI or those without revascularization (n=11).Conclusions: The incidence of in-hospital mortality with acute coronary syndrome is high in females, STEMI diagnosis, Killip Class I, and no revascularization.